Rise of the Anatolian Tigers : Turkey Urbanization Review, Main Report - World Bank (Washington, DC, 2015)
Turkey’s demographic and economic transformation has been one of the world’s most dramatic, with urban growth and economic growth proceeding hand in hand. Distinguishing Turkey from many other developing countries has been the pace, scale, and geographical diversity of its spatial and economic transformation. Fast-growing secondary cities bring added challenges that define Turkey’s second-generation urban agenda. New and differentiated service standards will need to be established across both dense urban built-up areas and small villages and rural settlements within the newly-expanded metropolitan municipality administrative area. These developments make planning, connecting, and financing important policy principles for Turkey’s second-generation urban development agenda. This policy brief frames a second-generation urban development agenda to support Turkey’s transition from upper middle income to high income.